Interior design visual presentation : a guide to graphics, models, and presentation methods - Mitton, Maureen (2018)
"A newly updated and comprehensive guide to all aspects of visual design"--
Includes bibliographical references and index.
Keywords: Interior decoration rendering; Interior decoration -- Design; ARCHITECTURE / Interior Design / General